PUISI BERHUMOR: STRATEGI TUTUR REMY SYLADO - Basori, NFN (SUAR BETANG, 2017)
Poetry, as well as other literary works, is a speech. If poetry is a speech, it indicates the presence speaker and hearer. In this study, a poetry as speech is examined using pragmatic theories which include implicatures, language play, as well as the implications of the meaning to the reader as a hearer. This study will describe the Remy Sylado strategy and skill in the use of language elements in the creation of poetry that has the effect of humour for readers. The theory is used to dissect the data is pragmatic theory relating to implicature, cooperative principle, and politeness principle. The use of cooperative and politeness principle concerned with the analysis that these poems can be included in the category of humour. In general, humour was identified as a symptom that violates the language. The principle of inequality, unpredictability, and pornography is a humour characteristic. This carefully situations produced four strategies used by Remy Sylado to convey his ideas to the reader, namely puns, pornography, slip of the tongue, and unpredictability.